Práticas Docentes e Ensino Religioso: uma análise da relação entre o modelo de Ensino Religioso não confessional e as práticas de professores em escolas da Rede Municipal de Educação de Anápolis, Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This research is entitled Teaching Practices and Religious Education: an analysis of the relationship between the non-denominational Religious Education model and the teaching practices in the Municipal Education Network of Anápolis, Goiás. The problematization of the research consists in knowing what the teaching practices of Religious Education are like in 3 (three) municipal schools in Anápolis/GO, considering the non-confessional model. The general objective is to reveal how non-denominational Religious Education happens in the teaching practice in 3 (three) municipal schools in Anápolis. For this purpose, authors such as: Aquino (2014), Castro (2009; 2015), Junqueira (2001); Gil Filho and Junqueira (2005); Dissenha and Junqueira (2013), Mantoan (2017), Sepulveda, Sepulveda and Fernandes (2015), Skliar (2003), were used to constitute the theoretical basis, among others. The methodology used in the project approaches the phenomenological method, with a qualitative, exploratory, bibliographical and field approach. As a technique for data collection, we used narrative interviews with teachers from 3 (three) municipal schools in the northern region of Anápolis. To reach the sense units, the narratives were intertwined with the Curricular Document for Religious Education in the Municipal Education Network of Anápolis, Goiás (Anápolis, 2020). The results achieved made it possible to understand that the practices in Religious Education are centered on contents that refer to religious diversity, which is interpreted by different themes, such as: spiritual culture, educational didactic material and mediation of socio-emotional conflicts. It is concluded that the teaching practices are based on religious diversity as a promoter of alterity, dialogue and respect. Teachers base their practices on different types of knowledge, such as philosophical, theological and historical by doing research on educational didactic material for their classes and are attentive to the socio-emotional demands of the students, since they seek to mediate problems of this nature.
Teaching Practices and Religious Education: an analysis of the relationship between the non-confessional Religious Education model and teacher practices in schools in the Municipal Education Network of Anápolis, Goiás
Keywords: Ensino Religioso - Práticas docentes; Diversidade religiosa - Espiritualidade; Laicidade; Religious Education - Teaching practices; Religious diversity - Spirituality; Secularity; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::TEOLOGIA